Physicochemical Characterization of Soils in Different Land Uses: A Case Study in Jatiroke Village, Sumedang, West Java - Nashifa Karisma Khanri; Nadia Putri Nur Asri; Hazel Abyudaya Hendra; Sindhy Susantya; Dimastian Hari Susetyo; Kartika Hajar Kirana; Dini Fitriani; Eleonora Agustine (Postgraduate, University of Mataram, 2025)
This study aimed to analyze the physicochemical characteristics of soils across different land uses in Jatiroke Village, West Java. Twenty-four surface soil samples were collected from rice fields, plantations, residential areas, and a temporary waste disposal site (TPS) using a stratified random sampling design. Parameters measured included soil color, texture, temperature, pH, electrical conductivity (EC), and total dissolved solids (TDS) through field and laboratory analyses. Principal Component Analysis (PCA) was applied to evaluate parameter relationships and identify dominant drivers of variability. Results showed that rice fields exhibited the highest salinity, primarily linked to the application of nitrogen- and potassium-based fertilizers, while TPS soils were affected by leachate containing organic and inorganic contaminants. Residential areas maintained near-neutral pH and low salinity, and plantations displayed intermediate variability. Descriptive traits such as color and texture varied across land uses but did not strongly differentiate soil conditions. PCA confirmed EC and TDS as the dominant differentiating factors, with pH and temperature contributing secondary variation. These findings demonstrate that fertilizer use and waste leachate are the main causes of elevated soil salinity, emphasizing the importance of monitoring EC and TDS for sustainable land management.